Did the changes made to the 2022-2024 code of points in trampoline gymnastics change the score of the gymnasts? - Kosova, S.; Kosova, M. K. (Science of Gymnastics Journal, 2024)
The evaluation rules for trampoline gymnastics were revised by the technical committee post-Tokyo 2020 Olympics, notably affecting the qualifying round. Previously, only four elements were considered for difficulty points in the first routine, but now all elements count in both routines. To assess the impact, data from the 28th/29th FIG Trampoline Gymnastics World Age Group Competitions and 35th/36th FIG Trampoline Gymnastics World Championships in 2021/2022 were analyzed. A t-test compared scores in Execution (E), Difficulty (D), Time Of Flight (TOF), and Horizontal Displacement (HD) between 2021 and 2022. In the senior men's category, average values increased in D, HD, and total scores in 2022, with significant differences in Execution and near-significant in TOF scores. Across all other categories, mean values of D, E, TOF, HD, and total scores rose in 2022, though without statistical significance. The trend towards higher scores under the new rules suggests their influence, yet unexplored factors may also play a role. Further research is needed for a comprehensive understanding.